Water potential characteristics and yield of summer maize in different planting patterns - L. Quanqi; C. Yuhai; L. Mengyu; Z. Xunbo; D. Baodi; Y. Songlie (Plant, Soil and Environment, 2008)
A study was conducted in the Shandong province in North China to investigate the effects of different planting patterns on water potential characteristics of soil-plant-atmosphere continuum (SPAC) and yield of summer maize. Three planting patterns were applied, i.e. bed planting (BE), furrow planting (FU) and flat planting (FL). The results showed that although soil moisture content in 0-20 cm soil layer in BE was decreased, soil temperature was increased; as a result, soil water potential in BE was increased. Compared with FL, leaf water potential in BE and FU was enhanced, but water transfer resistance between soil-leaf and leaf-atmosphere was decreased; feasible water supply conditions were thus created for crops colony. Maize yield of BE and FU was significantly (LSD, P < 0.05) higher than that of FL, by 1326.45 and 1243.76 kg/ha, respectively. These results obtained in field crop conditions support the idea that planting patterns affect soil water potential, leaf water potential, water transfer resistance between soil-leaf and leaf-gas of summer maize in North China.